2011
DOI: 10.1016/j.jcrs.2010.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Corneal thickness changes after corneal collagen crosslinking for keratoconus and corneal ectasia: One-year results

Abstract: No author has a financial or proprietary interest in any material or method mentioned. Additional disclosure is found in the footnotes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

21
141
3
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(169 citation statements)
references
References 40 publications
(64 reference statements)
21
141
3
4
Order By: Relevance
“…Similarly, Wollensak et al reported a reduction in the mean keratometry reading of 2.01 D (11) . Similar to previous studies, the corneal thickness decreased from the preoperative to the final time point, indicating corneal compaction (20,22,23) . In our study, statistically significant differences between the pre-and postoperative measurements were detected when the corneal thicknesses at the apex of the keratoconus (MCT) and pupil center (CCT) were measured.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, Wollensak et al reported a reduction in the mean keratometry reading of 2.01 D (11) . Similar to previous studies, the corneal thickness decreased from the preoperative to the final time point, indicating corneal compaction (20,22,23) . In our study, statistically significant differences between the pre-and postoperative measurements were detected when the corneal thicknesses at the apex of the keratoconus (MCT) and pupil center (CCT) were measured.…”
Section: Discussionsupporting
confidence: 89%
“…This finding was in all central readings including pupil centre, apex, and thinnest local pachymetry values and comparable to other studies. 14,15,18,21,28 There appears to be initial thinning, followed by a return to baseline at 1 year. Greenstein et al summarizes multiple factors that could contribute to this phenomenon.…”
Section: Discussionmentioning
confidence: 98%
“…Greenstein et al summarizes multiple factors that could contribute to this phenomenon. 28 Possibilities include epithelial remodeling, anatomic and structural changes of the corneal collagen fibrils, 29,30 alterations in corneal hydration 31 and edema, 32,33 keratocyte apoptosis, [34][35][36] and changes in glycosaminoglycans. 37 The centrifugal measurements of corneal thickness reflect the concept that at 6 months follow-up the more central readings are significantly thinner, but interestingly the 6 mm diameter measurements are no different.…”
Section: Discussionmentioning
confidence: 99%
“…Crosslinking studies with long-term follow-up have shown that corneal thickness as well as central keratometry follows a dynamic curve over the first 6 months. 7,8 Although complete epithelial healing is achieved in the first few days postoperatively, epithelium remodeling is an acceptable explanation for the continuous changes seen over several months. Avoidance of contact lens corneal bearing and mechanical trauma to the center of the cornea seems to be crucial for undisrupted epithelium remodeling and normal corneal nerve proliferation after CXL.…”
Section: Discussionmentioning
confidence: 99%